Therapeutic effects of tyroserleutide on lung metastasis of human hepatocellular carcinoma SK-HEP-1 and its mechanism affecting ICAM-1 and MMP-2 and -9 - Che, Xuchun (Drug Des Devel Ther, 2018)
BACKGROUND: Tyroserleutide (YSL) inhibits the growth and metastasis of human hepatocellular carcinoma (HCC). This paper studied the effect of YSL on metastasis of human HCC and investigated its mechanisms. METHODS: In vivo, experimental lung metastasis models of human HCC SK-HEP-1 cells in nude mice were established, and In vitro, the proliferation, adhesion and invasion of SK-HEP-1 cells were detected. RESULTS: In vivo, YSL significantly inhibited the metastasis of human HCC. In vitro, YSL significantly inhibited the proliferation, adhesion and invasion of SK-HEP-1 cells. Through analyses with reverse transcription PCR (RT-PCR) and Western blot, we observed that YSL significantly inhibited the expressions of ICAM-1 in SK-HEP-1 cells. Through RT-PCR, Western blot and zymography methods, YSL was discovered to decrease the mRNA level, protein expression and activity of MMP-2 and -9 in SK-HEP-1 cells. CONCLUSION: We concluded that YSL could inhibit tumor growth and metastasis of human HCC SK-HEP-1 cells.